تعزيز التنويع الإقتصادي لدعم إيرادات الدولة دراسة حالة الجزائر 2000-2020 - بن علية مبارك; طيبي محمد; بوجلال أحمد (جامعة عمار ثليجي الاغواط, 2022)
economic diversification has taken great importance as a strategy in Arab countries, including Algeria, especially in the light of the oil shock experienced by the oil-producing countries, which negate affected the financial budgets of those states, adding to this the oilwealth is classified as a wealth depleted, so Algeria has to find theeconomic sources in order to funding the public treasury which isalternative for petroleum economy, as it contributes to the diversificationof public revenues. Algeria has sought to pursue economic diversificationstrategy by investing in renewable energies as permanent and sustainableinvestments, and as well as working on the establishment of free industrial areas to encourage investment and to attract foreign capital, inaddition to its interest in investing in the tourism sector as a source of financing the public treasury. financing the public treasury.